Biodiesel production of WCO-neem oil and mixed using pilot plant scale with ultrasound and overhead stirred and characteristic of emissions in fire tube boiler - Suherman; Ilmi; M. Sabri; Edo Fransisko Ginting; Josua Jose Silalahi (Case Studies in Chemical and Environmental Engineering)
The boiler is one of the industrial machines that consumes the most fuel and boilers are significant contributors to air pollution. This study aims to compare the physicochemical properties of biodiesel a mixture of WCO oil and neem oil (70:30) using a pilot plant scale with different types of stirring (overhead and ultrasound). Subsequently, the produced biodiesel was tested for fuel consumption rate and exhaust emissions generated from combustion in a fire-tube boiler. The optimum yield was found using an ultrasound stirrer at a temperature of 60 °C, KOH loading 2 w/w%, with an molar ratio methanol to oil of 12:1 and a reaction time of 75 min, which is 98.70 %. The addition of neem oil to WCO oil increased the oxidative stability and reduced the pour point, and cloud point of WCONOME, by 184.85 %, 16.67 %, and 52 % respectively. Next, the ultrasound stirrer biodiesel with higher density and kinematic viscosity compared to the overhead stirrer, although the flash point and cetane number were lower. Increasing the biodiesel ratio in diesel fuel reduced exhaust emissions (CO, CO2, and HC) produced by the boiler. Interestingly, the exhaust emissions of WCONOME were lower than compared to palm biodiesel POME30. The physicochemical properties of WCONOME biodiesel have met the ASTM 6751 standard. Finally, biodiesel from a mixture of waste cooking oil and neem oil has great potential to replace diesel fuel as a fire-tube boiler fuel for generating green energy.